Optimalisasi Kombinasi Cabang Usahatani Tanaman Pangan untuk Memperoleh Pendapatan Maksimum di Wilayah Transmigrasi Km 38 Kelurahan Sei Gohong Kecamatan Bukit Batu Provinsi Kalimantan Tengah - Masniati Masniati; Dolok Saribu; Umi Salawati (Universitas Lambung Mangkurat, 2012)
This research aims is to determine farming patterns or optimized combination of existing sub farming to maximize income, to calculated farming cost and income of existing farming pattern, and to know farmer’s problems in applying optimized farming pattern. There are two dominant farming patterns in research area, i.e: (i) big chilly - small chilly – cucumber; and (ii) egg plant - string bean - tomato. Based on linear programming approach, the optimum farming pattern for the first pattern is big chilly - small chilly; and the second one is egg plant - tomato. After being optimized, the income of first pattern increases from Rp 7,930,521 to Rp 1,858,689.20 (30.61% increase). The income of second pattern also increasea 5.49% compared before reallocation. Total cost for one farming process of the first and second pattern is Rp 5.458,376.70 and Rp 5,484,635.70, respectively. After optimization, total cost can be reduced Rp 1,198,587.34 and Rp 550,102 for the first and second pattern, respectively. Farmer’s problems in applying optimized farming pattern are capital and farm area limitation, and price fluctuation for both input and output.